Dissolving differences: Law and water's role in legitimizing global hierarchies - Krohn, David (Institute of Marine and Environmental Law, 2025)
We live under the false illusion that there is an infinite supply of water on earth. In reality, quantities of available freshwater have remained constant for at least 2000 years while the global population has increased 33 fold during this same period. Rainfall remains the only form of renewable water resource and recycles around 45000 km3 of water per year, yet the world's population rises by around 85 million people per annum. Worryingly, World Bank estimates postulate a 56% increase in demand by 2025. As a result, the available quantity of water per capita is steadily decreasing and more than five million people, most of them children die every year from illnesses caused by drinking poor quality water. While at least one billion lack any access to clean water, North Americans use about 5,000 litres of water per person per day.